2023
DOI: 10.3389/fgene.2022.1068837
|View full text |Cite|
|
Sign up to set email alerts
|

A novel transcription factor-based signature to predict prognosis and therapeutic response of hepatocellular carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is one of the most common aggressive malignancies with increasing incidence worldwide. The oncogenic roles of transcription factors (TFs) were increasingly recognized in various cancers. This study aimed to develop a predicting signature based on TFs for the prognosis and treatment of HCC.Methods: Differentially expressed TFs were screened from data in the TCGA-LIHC and ICGC-LIRI-JP cohorts. Univariate and multivariate Cox regression analyses were applied to establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…Previous studies have identified TF-related gene signatures and risk score models in colorectal cancer, glioblastoma, breast cancer, endometrial cancer, ovarian cancer and gastric cancer, suggesting that TF-based signatures can predict prognosis and therapeutic efficacy for cancer patients [ 7 – 14 ]. In addition, a 2-TF prognostic signature with different clinical features and treatment preferences was constructed in HCC [ 15 ]. In the present study, we constructed a 9-TF prognostic signature and explored its potential to guide clinical treatment using completely different analytical strategies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have identified TF-related gene signatures and risk score models in colorectal cancer, glioblastoma, breast cancer, endometrial cancer, ovarian cancer and gastric cancer, suggesting that TF-based signatures can predict prognosis and therapeutic efficacy for cancer patients [ 7 – 14 ]. In addition, a 2-TF prognostic signature with different clinical features and treatment preferences was constructed in HCC [ 15 ]. In the present study, we constructed a 9-TF prognostic signature and explored its potential to guide clinical treatment using completely different analytical strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we constructed a 9-TF prognostic signature and explored its potential to guide clinical treatment using completely different analytical strategies. The AUC values of the 2-TF prognostic signature were 0.59–0.74 for 1-, 2- and 3-year OS in different databases according to Yang’s study [ 15 ]. In contrast, the AUC values of the 9-TF prognostic signature in our study were 0.695–0.826 for 1-, 2- and 3-year OS, indicating that the 9-TF prognostic signature we established may have better performance in predicting OS in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations